Bone xenotransplantation: A review of the history, orthopedic clinical literature, and a single‐center case series. (5th May 2020) - Bracey, Daniel N.; Cignetti, Natalie E.; Jinnah, Alexander H.; Stone, Austin V.; Gyr, Bettina M.; Whitlock, Patrick W.; Scott, Aaron T.
Abstract: Background: One‐half of all orthopedic surgeries require bone grafting for successful outcomes in fusions, reconstructive procedures, and the treatment of osseous defects resulting from trauma, tumor, infection, or congenital deformity. Autologous bone grafts are taken from the patient's own body and remain the "gold standard" graft choice but are limited in supply and impart significant patient morbidity. Xenograft bone is an attractive alternative from donors with controlled biology, in large supply and at a theoretically lower cost. Clinical results with xenograft bone for orthopedic applications have been mixed in the limited clinical trials published. Methods: In the current review, we introduce fundamental principles of bone grafting, systematically review all orthopedic clinical studies reporting outcomes on patients transplanted with xenograft bone, and we present our own clinical results from patients grafted with bovine bone in foot and ankle reconstructive procedures. Results: Thirty‐one clinical studies were identified for review and the majority (47%) were from spine surgery literature. Favorable results were reported in 44% of studies while 47% of studies reported poor outcomes and discouraged use of xenograft bone products. In our own clinical series, xenograft failed to integrate with host bone in 58% of cases and persistent pain was reported in 83% of cases. Conclusions: This is the first systematic review of clinical results reported after bone xenotransplantation for orthopaedic surgery applications. Current literature does not support the use of xenograft bone products and our institution's results are consistent with this conclusion. Our laboratory has reported promising pre‐clinical results with a xenograft product derived from porcine cancellous bone, but additional testing is required before considering clinical translation.